Microbiological analysis of the water provided to a Health Unit in the Municipality of Itajubá, Minas Gerais (Research, Society and Development, 2021)
Water quality control is one of the fundamental actions for disease prevention. One of the most frequent causes of death in the world is water-borne diseases, where the most commonly found contaminating bacteria are Acinetobacter spp, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus. The lack of potable water is not always noticeable to sight or smell, requiring a laboratory analysis to detect it. As water quality is an essential factor in maintaining human health, in health settings, it is necessary to confirm the quality of the water offered to patients. Thus, the point of collection of water samples was selected in a Health Unit located in the municipality of Itajubá, Minas Gerais. The analysis of the presence of total coliforms and Escherichia coli was performed using the Colilert® reagent, which is approved by the standard method for water and sewage analysis Standard Methods for the Examination of Water and Wastewater. The results were evaluated by changing the color indicating the presence or absence of total coliforms and E. coli. At the Health Unit, all samples were negative for total coliforms and the presence of E. coli, indicating that the samples are suitable for consumption. The objective of this work was to verify the microbiological quality of the water that is provided to a Health Unit and to warn of the importance of quality monitoring aiming at the prevention and dissemination of diseases that can further aggravate the situation of already debilitated patients.